Improving the Health, Safety, and Well-Being of Young Adults: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Young adults are at a significant and pivotal time of life. They may seek higher education, launch their work lives, develop personal relationships and healthy habits, and pursue other endeavors that help set them on healthy and productive pathways. However, the transition to adulthood also can be a time of increased vulnerability and risk. Young adults may be unemployed and homeless, lack access to health care, suffer from mental health issues or other chronic health conditions, or engage in binge drinking, illicit drug use, or driving under the influence. Young adults are moving out of the services and systems that supported them as children and adolescents, but adult services and systems2014for example, the adult health care system, the labor market, and the justice system2014may not be well suited to supporting their needs. Improving the Health, Safety, and Well-Being of Young Adults is the summary of a workshop hosted by the Board on Children, Youth, and Families of the Institute of Medicine (IOM) and the National Research Council (NRC) in May, 2013. More than 250 researchers, practitioners, policy makers, and young adults presented and discussed research on the development, health, safety, and well-being of young adults. This report focuses on the developmental characteristics and attributes of this age group and its placement in the life course; how well young adults function across relevant sectors, including, for example, health and mental health, education, labor, justice, military, and foster care; and how the various sectors that intersect with young adults influence their health and well-being. Improving the Health, Safety, and Well-Being of Young Adults provides an overview of existing research and identifies research gaps and issues that deserve more intensive study. It also is meant to start a conversation aimed at a larger IOM\/NRC effort to guide research, practices, and policies affecting young adults.

The Impact of Juvenile Justice System Involvement on the Health and Well-Being of Youth, Families, and Communities of Color: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Involvement with the juvenile justice system can impact young people's physical and mental health and well-being throughout their lives, as well as the health and well-being of their families and communities. Youth of color are more likely to become involved with the juvenile justice system, and suffer worse outcomes in sentencing, during incarceration, and after release. The National Academies of Sciences, Engineering, and Medicine's Roundtable on the Promotion of Health Equity convened a workshop to discuss the impact that juvenile justice system involvement has on the health and well-being of adolescents, families, and communities of color; examine policies that are successful in improving outcomes; and explore what needs to be done to improve all aspects of encounters with the juvenile justice system. The workshop suggested pursuing alternatives to traditional juvenile justice systems that would allow adolescents to stay in their communities rather than in detention, responding to behavioral problems in youth with interventions that promote health and positive development rather than punishment, and tailoring interventions and programming to participants' cultural background and gender identity. This report summarizes the proceedings of the workshop.

Social Media and Adolescent Health - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Social media has been fully integrated into the lives of most adolescents in the U.S., raising concerns among parents, physicians, public health officials, and others about its effect on mental and physical health. Over the past year, an ad hoc committee of the National Academies of Sciences, Engineering, and Medicine examined the research and produced this detailed report exploring that effect and laying out recommendations for policymakers, regulators, industry, and others in an effort to maximize the good and minimize the bad. Focus areas include platform design, transparency and accountability, digital media literacy among young people and adults, online harassment, and supporting researchers.

Mental Health, Substance Use, and Wellbeing in Higher Education: Supporting the Whole Student - National Academies of Sciences, Engineering,; Medicine
Student wellbeing is foundational to academic success. One recent survey of postsecondary educators found that nearly 80 percent believed emotional wellbeing is a \

Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer is the summary of a workshop convened by the Institute of Medicine's National Cancer Policy Forum in July 2013 to facilitate discussion about gaps and challenges in caring for adolescent and young adult cancer patients and potential strategies and actions to improve the quality of their care. The workshop featured invited presentations from clinicians and other advocates working to improve the care and outcomes for the adolescent and young adult population with cancer. Cancer is the leading disease-related cause of death in adolescents and young adults. Each year nearly 70,000 people between the ages of 15 and 39 are diagnosed with cancer, approximately 8 times more than children under age 15. This population faces a variety of unique short- and long-term health and psychosocial issues, such as difficulty reentering school, the workforce, or the dating scene; problems with infertility; cardiac, pulmonary, or other treatment repercussions; and secondary malignancies. Survivors are also at increased risk for psychiatric conditions such as anxiety, depression, substance abuse, and suicide and may have difficulty acquiring health insurance and paying for needed care. Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer discusses a variety of topics important to adolescent and young adult patients with cancer, including the ways in which cancers affecting this group differ from cancers in other age groups and what that implies about the best treatments for these cancer patients. This report identifies gaps and challenges in providing optimal care to adolescent and young adult patients with cancer and to discuss potential strategies and actions to address them.

Public Health Consequences of E-Cigarettes - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Millions of Americans use e-cigarettes. Despite their popularity, little is known about their health effects. Some suggest that e-cigarettes likely confer lower risk compared to combustible tobacco cigarettes, because they do not expose users to toxicants produced through combustion. Proponents of e-cigarette use also tout the potential benefits of e-cigarettes as devices that could help combustible tobacco cigarette smokers to quit and thereby reduce tobacco-related health risks. Others are concerned about the exposure to potentially toxic substances contained in e-cigarette emissions, especially in individuals who have never used tobacco products such as youth and young adults. Given their relatively recent introduction, there has been little time for a scientific body of evidence to develop on the health effects of e-cigarettes. Public Health Consequences of E-Cigarettes reviews and critically assesses the state of the emerging evidence about e-cigarettes and health. This report makes recommendations for the improvement of this research and highlights gaps that are a priority for future research.

Promoting Positive Adolescent Health Behaviors and Outcomes: Thriving in the 21st Century - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Adolescence is a critical growth period in which youth develop essential skills that prepare them for adulthood. Prevention and intervention programs are designed to meet the needs of adolescents who require additional support and promote healthy behaviors and outcomes. To ensure the success of these efforts, it is essential that they include reliably identifiable techniques, strategies, or practices that have been proven effective. Promoting Positive Adolescent Health Behaviors and Outcomes: Thriving in the 21st Century identifies key program factors that can improve health outcomes related to adolescent behavior and provides evidence-based recommendations toward effective implementation of federal programming initiatives. This study explores normative adolescent development, the current landscape of adolescent risk behavior, core components of effective programs focused on optimal health, and recommendations for research, programs, and policies.

School-Based Strategies for Addressing the Mental Health and Well-Being of Youth in the Wake of COVID-19 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
COVID-19, along with heightened racial trauma, has caused unprecedented disruption in the lives of youth aged 10-18, leading them to experience increases in mental health concerns. Addressing these negative impacts requires that education leaders, school districts, state and local decision makers, parents, teachers, and youth work together to ensure that young people have the support and resources needed to address their mental, emotional, and behavioral health needs in the wake of the COVID-19 pandemic. This rapid expert consultation identifies school-based strategies for addressing the mental health and well-being challenges among youth that arose or were exacerbated during the COVID-19 pandemic. Included are strategies designed to support the holistic needs not only of youth but also of educators and staff. This rapid expert consultation was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation and the Alfred P. Sloan Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. The associated workshop series that informed the development of this rapid expert consultation was hosted by the National Academies' Forum for Children's Well-Being.

Investing in the Health and Well-Being of Young Adults - Institute of Medicine; National Research Council (The National Academies Press, 2015)
Young adulthood - ages approximately 18 to 26 - is a critical period of development with long-lasting implications for a person's economic security, health and well-being. Young adults are key contributors to the nation's workforce and military services and, since many are parents, to the healthy development of the next generation. Although 'millennials' have received attention in the popular media in recent years, young adults are too rarely treated as a distinct population in policy, programs, and research. Instead, they are often grouped with adolescents or, more often, with all adults. Currently, the nation is experiencing economic restructuring, widening inequality, a rapidly rising ratio of older adults, and an increasingly diverse population. The possible transformative effects of these features make focus on young adults especially important. A systematic approach to understanding and responding to the unique circumstances and needs of today's young adults can help to pave the way to a more productive and equitable tomorrow for young adults in particular and our society at large. Investing in The Health and Well-Being of Young Adults describes what is meant by the term young adulthood, who young adults are, what they are doing, and what they need. This study recommends actions that nonprofit programs and federal, state, and local agencies can take to help young adults make a successful transition from adolescence to adulthood. According to this report, young adults should be considered as a separate group from adolescents and older adults. Investing in The Health and Well-Being of Young Adults makes the case that increased efforts to improve high school and college graduate rates and education and workforce development systems that are more closely tied to high-demand economic sectors will help this age group achieve greater opportunity and success. The report also discusses the health status of young adults and makes recommendations to develop evidence-based practices for young adults for medical and behavioral health, including preventions. What happens during the young adult years has profound implications for the rest of the life course, and the stability and progress of society at large depends on how any cohort of young adults fares as a whole. Investing in The Health and Well-Being of Young Adults will provide a roadmap to improving outcomes for this age group as they transition from adolescence to adulthood.

Responding to the Current Youth Mental Health Crisis and Preventing the Next One: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Across the country, mental health concerns are affecting children and youth in every community. Mental health providers are witnessing increased numbers of patients and increased severity in reported concerns. In the midst of this crisis, communities are exploring strategies for addressing children and youth's mental health, including increased investment in prevention. Given this current crisis, and the unprecedented response and potentially increased funding, there are opportunities to learn how to better incorporate prevention and promotion strategies into systems and programs for children and youth support. To explore these opportunities, the National Academies' Forum for Children's Well-Being held a 3-day workshop in May 2022. This Proceedings of a Workshop-in Brief provides a high-level summary of the topics addressed in the workshop.

The Promise of Adolescence: Realizing Opportunity for All Youth - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Adolescence2014beginning with the onset of puberty and ending in the mid-20s2014is a critical period of development during which key areas of the brain mature and develop. These changes in brain structure, function, and connectivity mark adolescence as a period of opportunity to discover new vistas, to form relationships with peers and adults, and to explore one's developing identity. It is also a period of resilience that can ameliorate childhood setbacks and set the stage for a thriving trajectory over the life course. Because adolescents comprise nearly one-fourth of the entire U.S. population, the nation needs policies and practices that will better leverage these developmental opportunities to harness the promise of adolescence2014rather than focusing myopically on containing its risks. This report examines the neurobiological and socio-behavioral science of adolescent development and outlines how this knowledge can be applied, both to promote adolescent well-being, resilience, and development, and to rectify structural barriers and inequalities in opportunity, enabling all adolescents to flourish.